2020
DOI: 10.1111/eve.13250
|View full text |Cite
|
Sign up to set email alerts
|

An online survey investigating perceived prevalence and treatment options for stereotypic behaviours in horses and undesirable behaviours associated with handling and riding

Abstract: In the horse, inappropriate management and training, as well as pain, frustration, fear and anxiety can result in undesirable behaviours. Common undesirable behaviours include pawing, striking, rearing, kicking, bolting, bucking, shying, napping, freezing, biting and bite threats, as well as a range of oral and locomotive stereotypic behaviours. Many of these behaviours are dangerous for the human handlers and can be unhealthy and harmful for the horse; for safety and welfare reasons, they must be rapidly addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Traditional equestrianism has been commonly associated with failures to consider horses' social needs. Most equestrian activities require riders to overcome their mount's innate liking for conspecific company and cannot afford unfamiliar horses to exercise agency when meeting under-saddle [34]. Denying social needs and normal greeting styles can lead to undesirable responses under-saddle.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional equestrianism has been commonly associated with failures to consider horses' social needs. Most equestrian activities require riders to overcome their mount's innate liking for conspecific company and cannot afford unfamiliar horses to exercise agency when meeting under-saddle [34]. Denying social needs and normal greeting styles can lead to undesirable responses under-saddle.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst any type of sedation may reduce potentially dangerous behaviours, and hence, improve human safety, thoughtful selection of the sedating agent is critical for addressing the horse-welfare aspect [ 130 ]. Using agents for chemical restraint during potentially fear-inducing procedures without ensuring the agent is anxiolytic has the potential to cause further fear, stress, and aversive learning [ 128 ].…”
Section: Moving Forward To Improve Horse Experiences During Husbandry...mentioning
confidence: 99%
“…Importantly, the undesirable behaviours may not be limited to veterinary visits—many owners struggle with their horse’s behaviour at home, and may seek out behavioural advice from their veterinarian. One study reported that over 77% of respondent veterinarians considered owner complaints of “difficult” or “uncooperative” horses to be common (57.1%) or extremely common (20.4%) [ 130 ].…”
Section: Moving Forward To Improve Horse Experiences During Husbandry...mentioning
confidence: 99%
“…This breeding is associated with various types of activities carried out by humans. Some of the activities are negative for animals’ welfare, such as the necessity of social isolation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%